Microbiological investigation of honey collected from Şırnak province of Turkey - ERKAN, M. E.; VURAL, A.; GURAN, H. S.; DURMUSOGLU, H. (Journal of the Hellenic Veterinary Medical Society, 2017)
In this study, 50 randomly selected honey samples purchased from different retail markets in Şırnak, Turkey, were investigated for microbiological quality and probable public health risks. The honey samples were tested for the presence and enumeration of vegetative and spore forms of total mesophilic aerobic bacteria, total mesophilic anaerobic bacteria, sulfite reducing anaerobic bacteria, Clostridium botulinum, Clostridium perfringens and Bacillus cereus according to standard techniques. C. botulinum, C. perfringens and sulfite reducing anaerobic bacteria spores were not detected in the analyzed honey samples. The contamination rate of vegetative form of B. cereus, sulfite reducing anaerobic bacteria, total mesophilic aerobic bacteria and total mesophilic anaerobic bacteria were found to be 4%, 4%, 86% and 44%, respectively. The spore form of B. cereus, total mesophilic aerobic bacteria and total mesophilic anaerobic bacteria contamination rate were detected as 2%, 84% and 42%, respectively. It is concluded that, during the production, storage, and sales, honey samples may be contaminated with some microorganisms from different sources, causing important public health risks.